Land use and alpha, beta, and gamma diversity of Diplopoda in the Otún basin, Colombia. - Ruiz-Cobo, Darío Hernán; Grupo Gestión en Agroecosistemas Tropicales Andinos (GATA), Facultad de Ciencias Ambientales, Universidad Tecnológica de Pereira. Vereda La Julita A.A. 97, Pereira (Pontificia Universidad Javeriana, 2010)
Objective: To determine the relationship between changes in ecosystems and agrosystems provoked by human intervention and the alpha, beta and gamma diversity of the Diplopoda in the middle basin of the Otún river. Materials and methods: In this research we used a stratified systematic design with seven sampling windows and 16 sampling points. Millipedes were divided into families and morphotypes to calculate the alpha, beta and gamma diversity related to the heterogeneity of land uses. Results: We identified 35 morphotypes from 12 families and five orders. Alpha diversity of Diplopoda revealed significant differences between land uses (P <0.05) and a decrease of richness from preserved areas to transformed areas by human activity. A high number of exclusive morphotypes were found in forest relicts and fallow with low species turnover between them, while the pastures, crop fields and plantations presented similar numbers of morphotypes but the species turnover between them was high (complementarity > 85%) in spite of the low diversity in the land uses, which determined the high contribution of the beta diversity to the gamma diversity of the landscape. Conclusion: The heterogeneity of land uses showed that the changes modify the structure of diversity in Diplopoda with gradients diverging from the preserved ones to the highly transformed ones. Key words: alpha, beta, gamma diversity, Colombian Andes, soil Diplopoda.